The role of atomic carbon in directing electrochemical CO(2) reduction to multicarbon products. Issue 1 (23rd December 2020) - Peng, Hongjie; Tang, Michael T.; Liu, Xinyan; Schlexer Lamoureux, Philomena; Bajdich, Michal; Abild-Pedersen, Frank
Abstract : Atomic carbon plays a role in steering selectivity in electrochemical carbon mono-/dioxide reduction. Appropriate binding strengths of CO and C, combined with four-fold sites, constitute fundamental features toward selective multicarbon production. Abstract : Electrochemical reduction of carbon-dioxide/carbon-monoxide (CO(2) R) to fuels and chemicals presents an attractive approach for sustainable chemical synthesis, but it also poses a serious challenge in catalysis. Understanding the key aspects that guide CO(2) R towards value-added multicarbon (C2+ ) products is imperative in designing an efficient catalyst. Herein, we identify the critical steps toward C2 products on copper through a combination of energetics from density functional theory and micro-kinetic modeling. We elucidate the importance of atomic carbon in directing C2+ selectivity and how it introduces surface structural sensitivity on copper catalysts. This insight enables us to propose two simple thermodynamic descriptors that effectively identify C2+ selectivity on metal catalysts beyond copper and hence it defines an intelligible protocol to screen for materials that selectively catalyze CO(2) to C2+ products.